Exploring the theoretical link between cultural and emotional intelligence: A system analysis for human resource management - P. Jonck; E. Swanepoel (South African Journal of Business Management, 2015)
In light of increasing globalisation and a changing workforce, the ability to bridge cultural fissures separating diverse groups will be increasingly critical to sustained work place well-being, especially with relation to global competitiveness and economic growth. This article explores the link between cultural and emotional intelligence in an effort to investigate the possibility of measuring, developing, and effectively managing individual responses to cultural influences that give rise to significant tension within the organisational context. Since South Africa's heterogeneous workforce is characterised by culturally diverse group interaction, the conceptualisation of a cross-cultural facet of intelligence with emotional-management as reciprocal component has practical implications towards optimal intercultural organisational harmony, effective globalised interaction and overall group-dynamics.
Keywords: 650